Information System Strategy for Improving Academic Service Quality at UM Banjarmasin Through the Development of Academic Extension (ADEX) Innovation Application - Kamarudin, Kamarudin (Universitas Aisyiyah Surakarta, 2025)
This research program aims to enhance academic service quality at Universitas Muhammadiyah Banjarmasin (UM Banjarmasin) through the development of an innovative application called Academic Extension (ADEX). The initiative was driven by the need to improve efficiency and integration of academic services, addressing the current inadequate systems that fail to support effective academic management. The research methodology involved three key phases: needs analysis, application development, and field testing. ADEX incorporates various features to streamline academic management, including schedule management, attendance tracking, and communication channels between faculty members and students. The implementation of ADEX has demonstrated significant improvements in both efficiency and quality of academic services at UM Banjarmasin, delivering tangible benefits to the entire academic community. Results indicate that the integration of ADEX has successfully addressed the initial challenges, providing a comprehensive solution for academic service management while enhancing the overall educational experience for both faculty and students.